THE IMPACT OF TOTAL INTRAVENOUS ANESTHESIA VERSUS INHALATIONAL ANESTHESIA ON POSTOPERATIVE COGNITIVE DYSFUNCTION IN ELDERLY PATIENTS - TARIQ , A; IQBAL , F; YOUNUS , Z; CHAUDHARY , WA (Biological and Clinical Sciences Research Journal, 2023)
Postoperative cognitive dysfunction (POCD) is a common complication among elderly patients undergoing surgery. Anesthesia type has been suggested as a potential factor influencing the occurrence of POCD. This study aims to investigate and compare the impact of total intravenous anesthesia (TIVA) and inhalational anesthesia on the development of POCD in elderly patients. The primary aim of this study is to assess and compare the incidence of POCD in elderly patients receiving TIVA or inhalational anesthesia during surgical procedures. The secondary objectives include evaluating the duration of cognitive impairment, perioperative clinical parameters, and potential risk factors contributing to POCD. This prospective cohort study will enroll elderly patients (65 and above) scheduled for elective surgery. Participants will be divided into two groups: one receiving TIVA and the other receiving inhalational anesthesia. Preoperative, intraoperative, and postoperative data will be collected and analyzed. Cognitive function will be assessed using standardized neuropsychological tests before surgery and at specified postoperative intervals. Additionally, perioperative clinical parameters, anesthesia-related data, and potential risk factors for POCD will be recorded and analyzed. The study results will include the incidence of POCD in both groups and the duration and severity of cognitive impairment. Perioperative clinical parameters, such as length of surgery and anesthesia duration, will be compared. Additionally, risk factors for POCD, such as age, comorbidities, and type of surgery, will be evaluated to identify their association with the development of cognitive dysfunction. This study will provide valuable insights into the impact of total intravenous anesthesia versus inhalational anesthesia on postoperative cognitive dysfunction in elderly patients. The findings will help anesthesiologists and surgeons make informed decisions regarding anesthesia for this vulnerable population, ultimately improving patient outcomes and quality of care.